(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The purpose of this study is to form an entrepreneurial spirit among Economics College of Indragiri students. The method used is an entrepreneurship internship for sixty days. Students are required to create a group consisting of several people and then submit a business proposal which is assessed as feasible by the reviewer, after being declared feasible, the business to be opened is bailed out by the Economics College of Indragiri. Students must return the funds after the entrepreneurship internship is complete. The findings of this study are the changing mindsets of students who take part in entrepreneurship internships to be more interested in opening a business than being an employee. This study can be used by college students to form an entrepreneurial spirit. This entrepreneurship internship forms students who have business management experience that will be their basic capital in opening a business after graduating from college.